PENERAPAN TOTAL QUALITY MANAGEMENT (TQM) DI SEKOLAH ISLAM - Wibowo, Rochmat Cahyo; Misbah, Muhammad (Jurnal Lingkar Mutu Pendidikan, 2025)
This study aims to describe the implementation of Total Quality Management (TQM) principles in enhancing the quality of the learning process at SMP Muhammadiyah Ajibarang and to formulate effective strategies to overcome challenges. A qualitative literature review methodology was employed, analyzing books, journal articles, and official documents related to TQM planning, implementation, and evaluation. The theoretical framework covers vision and mission development, SMART-based quality objectives, monitoring and evaluation systems, quality planning, risk management, and Weakness–Threat (WT) analysis. Findings indicate that applying leadership, involvement of all school members, process approach, and data-driven decision-making fosters continuous improvement. Monitoring through the report card system, evaluation meetings, and program reporting supports transparency and accountability. However, obstacles such as resistance to change, resource constraints, and uneven understanding of TQM present significant barriers. To overcome these issues, socialization, teacher training, efficient resource management, and integration of Islamic values into every stage of quality management are recommended. Consistent implementation of the Plan–Do–Check–Act (PDCA) cycle is expected to strengthen a quality culture, increase stakeholder satisfaction, and foster students’ moral character. It highlights enhanced teacher professionalism and competitive school branding. The study proposes a TQM implementation model integrated with Islamic values and practical guidance for optimal PDCA application.